PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN TINGKAT KECEMASAN PADA IBU NIFAS DI BPM ROSITA PEKANBARU - Fajar Sari Tanberika; Wira Ekdeni Aifa; Nia Desriva (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Anxiety is an emotional experience that is felt by individuals as unpleasant. Many factors cause a postpartum mother to experience anxiety and stress. One of the methods used to reduce the anxiety level of postpartum mothers is by giving classical music therapy. The purpose of this study was to determine the effect of classical music therapy on reducing anxiety levels in postpartum mothers at BPM ROSITA Pekanbaru .This research design uses a quasi-experimental methodwith Non Equivalent design pretest-posttestwith control group with a sample of 30 respondents consisting of 15 people in the experimental group and 15 people in the control group .Anxiety levels were measured using a questionnaire. The results of the statistical test used were paired T -test, Wilcoxon and Mann test–Whitney and obtained p value 0.000 (p 0.05). The results of the paired T -test showed that the experimental group before classical music therapy was given the mean value was 19.40 and experienced a decrease in anxiety levels after classical music therapy was given, namely 1 3.87 . In the control group there was no change with a p value of 0.878 (p 0.05). The Mann-Whitney test shows that classical music therapy has a significant effect on reducing anxiety levels in postpartum mothers . Hopefully with good information and guidancefrom the health center orand innovative services from posyandu cadresso that classical music therapy can be used to reduce anxiety levels in postpartum mothers.